Nutritional Analysis of Five Wild Edible Vegetables Traditionally Consumed by the Orang Asli in Perak - Rachel Thomas Tharmabalan (International Journal of Food Science)
The significance of wild edible plants may be traced back to antiquity, and methodological studies are the focus of present food movements to restore culinary traditions. Ethnobotanical appraisal was first done to determine the names and the significance of the five wild edibles used by the Orang Asli, which were Erechtites valerianiaeolia (Link ex Spring) DC, Dendrocalamus asper (Schult.) Backer, Solanum nigrum L., Gomphandra quadrifida (Blume) Sleumer, and Pleocnemia irregularis (C. Presl) Holttum collected from Sungkai, Perak in Malaysia. These wild edibles were then assessed for their proximate and mineral compositions. The present study revealed that the fiber content present in these wild edibles ranged from 2.7 to 12.5 g/100 g, whereas the protein content ranged from 1.8 to 6.8 g/100 g with Gomphandra quadrifida containing the highest amount of fiber and Solanum nigrum recording the highest protein content among the 5 wild edibles. In regard to the micronutreint content, iron was the highest in Gomphandra quadrifida, followed by Pleocnemia irregularis. Calcium and magnesium contents were the highest in Solanum nigrum. The results obtained in this study echo the urgency to conserve these plants in order to promote consumption as well as to improve the health and nutritional status of the Orang Asli.